PRINCIPLES OF SUSTAINABLE ARCHITECTURE IN THE PRODUCTION OF BAMBOO WOVEN WALL MATERIALS (DENDROCALAMUS ASPER) - Muhammad Zakaria Umar; Muhammad Arsyad; Santi Santi; Arman Faslih (SINERGI, 2020)
Bamboo is a sustainable building material because the use of new materials is sustainable. In the City of Kendari, there are still craftsmen of bamboo woven wall material. This research is important to do because to reveal how to make bamboo woven wall material by local craftsmen in Kendari and to find out the pattern of making bamboo woven wall material against the principles of sustainable architecture. This research is aimed at identifying and reviewing work tools, work materials, and how to make bamboo woven wall material against the principles of sustainable architecture by local craftsmen in Kendari City. This study uses a case study method with a qualitative approach. This study concluded that the principles of sustainable architecture in bamboo woven wall materials are as follows: working tools are used simply to reduce the use of new materials, the materials for making come from vegetation grown so that the location and natural resource ecosystems are sustainable, and how to make use of human energy so that it saves energy.